The Effect of Problem Based Learning Model Assisted by Media Based on Quizizz Application on Analytical Thinking Ability of Class X Students at SMA Negeri 16 Samarinda - Jailani; Rahmi, Nur; Purwati, Sri; Lumowa, Sonja V. T. (Biosel Biology Science and Education, 2024)
The use of media-assisted learning models such as PBL combined with quizizz can increase students' capacity to carry out analysis. This research aims to determine students' analytical thinking abilities after implementing the problem based learning model assisted by quizizz media. The type of research is a quasi-experiment with a nonequivalent pretest-posttest control group design model with the research population being all students of SMA Negeri 16 Samarinda, totaling 316 students. Samples were taken using a purposive sampling technique, so that class X-1 was selected as the experimental group and class X-6 as the control group with a total of 26 students each. The data analysis technique uses an independent samples t test at a significance level of 5% with the help of SPSS version 25 for Windows. The test results show a sig value. 0.000 < 0.05, which means that problem based learning assisted by media based on the quizizz application has an effect on the analytical thinking abilities of class X students at SMA Negeri 16 Samarinda. Keywords: Problem Based Learning, Quizizz, Analytical Thinking